ANALYSIS OF QUALITY CONTROL OF SUITCASES TO MINIMIZE DEFECTS USING THE CONTROL MAP METHOD AND FMECA (FAILURE MODE EFFECT AND CRITICALITY ANALYSIS) PT. MITRA MUTU ABADI - Firmansyah, Enricho; Sulistiyowati , Wiwik (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: So that the purpose of this research is to determine the level of disability a product by identifying the highest levels of risk a failure that arise and do the proposed fixes. Method: The Method employed is that This study using of qualitative and quantitative methods with those maps control p used to see the control over control and a lower. If the data is still within the limits of control, control data will be declared. A method of FMECA ( failure mode effect criticality and Analysis) knows the value of an RPN (Risk Priority Number) analysis and the critical of any potential failure products, as for tools help the pareto seventools includes diagrams, check sheet, diagrams and effect, histogram, stratification, control a chart and fishbone diagrams. Results: The key Results achieved are that The results of this study show the value on the hinge control map, known UCL with a value of 0.066, LCL with a value of 0.045, CL with a value of 0.055. On the casing control map, it is known that UCL with a value of 0.049, LCL with a value of 0.031, CL with a value of 0.040. On the handle defect control map, it is known that UCL with a value of 0.042, LCL with a value of 0.025, CL with a value of 0.033. In the hinge defect with the cause of failure, namely the production operator is not careful or less focused with an RPN value of 168 included in the high category. For the second on casing defects with the cause of failure, namely the provision of glue is uneven with an RPN value of 126 included in the high category. To get the best quality results, improvements can be made, namely the need to evaluate the comfort at work, because the more comfortable the workplace the concentration of workers is increasing, must choose materials that are strong, durable and have been tested for quality. need to update machines or tools with the latest technology. increase air circulation in the room and do greening around the company. before starting work activities the supervisor must brief the SOP, in the room given the SOP board. These improvements can minimize defects and can increase company productivity so that it can achieve the desired target. Novelty: The Novelty is derived from the specific application and detailed findings of the Control Chart and FMECA methods in addressing the rising defect rate at PT. Mitra Mutu Abadi.